Estudo comparativo de ciclo de vida e custo de pilar com diferentes traços de concreto - Silva, Aline de Oliveira (2014)
The sustainability of concrete structures is fundamental in search for sustainability in construction sector, since this material composed most of Brazilian works. Therefore, it is necessary information about environmental and economic performance of product to define the best strategy for each project. As from life cycle and costing assessment it is possible search and quantify the cost and environmental impact from each life cycle stage, cradle-to-grave, providing base to compare different products with the same function. This research used these tools to know the performance of a reinforced concrete column, cradle-to-gate, with two characteristic compressive strength, 30 and 50 MPa, and different concrete mixes, composed of three types of Portland cements: pozzolanic-compound (CP II-Z), pozzolanic (CP IV) and high early strength (CP V-ARI). It was concluded the strength level has more influence on the sustainability than the cement type, for the three studied ones. Furthermore, when considering each singly environmental parameter it was find that there was no best choice of pillar. When considering the integration of all parameters analyzed, the best alternative was CP-IV cement type and 50 MPa characteristic strength level. The unitary compressive strength analysis, per MPa, demonstrated 64% mean decrease for the cost and total environmental impact, when the characteristic strength increased from 30 MPa to 50 MPa.